Socialization of Waste Sorting and Utilization: Sosialisasi Pemilahan dan Pemanfaatan Sampah - Shodiq, Ja’far; Akbar, Ali; Firdaus, Rachmat; Huesein, Wa Ode Asma’ul Husna (Procedia of Social Sciences and Humanities, 2022)
Dissemination of waste sorting and utilization activities was carried out to residents of Dayurejo Village, precisely Gamoh Hamlet, Prigen District, Pasuruan Regency from January to March 2022. The purpose of this activity is to increase knowledge and skills regarding the sorting and utilization of household waste as a more useful product. The method of activity carried out is by conducting socialization counseling and providing examples of the use of plastic waste into hanging gardens. From this activity, it can be seen that the enthusiasm of the participants to acquire skills and abilities regarding the use of household waste. Likewise, the youths were very enthusiastic in participating in the socialization and counseling activities on household waste management. The stimulus to utilize the existing waste was responded well by the participants, thus giving hope for efforts to improve the quality of waste processing and reduce the negative impact of household waste and can produce more beneficial outcomes from household waste that is produced every day.